SISTEM KONTROL SUHU DAN KELEMBAPAN OTOMATIS PADA BUDIDAYA JAMUR TIRAM BERBASIS IOT UNTUK MENDUKUNG SMART FARMING SYSTEM - Muhamad Maksum Hidayat; Nur Fitrianingsih Hasan; Intan Maya; Martalina Wakerwa (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
The cultivation of mushrooms, particularly the oyster mushroom variety, is gaining increasing popularity within the agricultural sector in Indonesia. The success of oyster mushroom cultivation is highly dependent on environmental factors, notably temperature and humidity, which must be consistently maintained. In response to these challenges, this research is centered on the design and implementation of an IoT-based automated temperature and humidity control system aimed at supporting the concept of house smart farming. The system developed in this research consists of temperature and humidity sensors connected to an ESP32 microcontroller. Furthermore, this system is equipped with a user interface based on a mobile application accessible through Android devices. With this system in place, farmers can monitor the environmental conditions of their mushroom growth facilities in real-time and adjust temperature and humidity easily through the mobile application. The system's key strength lies in its capability to monitor environmental conditions in real-time, allowing farmers to conveniently observe temperature and humidity levels in their mushroom cultivation facilities remotely. Additionally, the system can autonomously adjust temperature and humidity through the mobile application. The research findings conclusively demonstrate that this system can maintain the required ideal temperature and humidity levels for successful oyster mushroom cultivation.